(untitled) (Editora Impacto Científico, 2025)
Innovative practices in Education need to be reflected upon and first involve a specific analysis of Technology concepts, new methodologies and curricula, as well as the way in which these three important educational elements can interact in the teaching and learning process, enhancing pedagogical practices and the global results, which need to be consolidated periodically. In this way, the present work aims to understand the interactivity of these three educational elements after understanding the separate concepts. Therefore, for the development, firstly a qualitative bibliographical research was carried out on some academic materials and subsequently reported an innovative innovative practice for the use of google forms, codes of ethics and simulations of recruitment and selection processes in a discipline called Ethics and Organizational Citizenship within the Business Administration Technician course. In the end, it was concluded that there was the presence of interactivity and innovation in the teaching-learning process, based on the relationship of Technology, Curriculum and new methodologies, making the learning generated meaningful and close to a real situation, in the business context.